2016
DOI: 10.1111/ajt.13902
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Causes Resistance to Anti-CD20–Mediated B Cell Depletion

Abstract: B cells play a central role in antibody-mediated rejection and certain auto-immune diseases. However, B-cell-targeted therapy such as anti-CD20 B cell-depleting antibody(aCD20) has yielded mixed results in improving outcomes. In this study, we investigated whether an accelerated B-cell reconstitution leading to aCD20 depletion-resistance could account for these discrepancies. Using a transplantation model, we found that antigen-independent inflammation, likely through TLR signals, was sufficient to mitigate B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Because CD20 depletion is short-lived in transplant contexts, 24 dosing was repeated on days 2, 7, 14, and 21. Peripheral blood B cells rose after LT in mice in the Iso group, but B cells were almost completely depleted by aCD20 in the blood and allograft ( Figure 7A,B).…”
Section: B Cell Depletion Attenuates Ar and Chronic Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Because CD20 depletion is short-lived in transplant contexts, 24 dosing was repeated on days 2, 7, 14, and 21. Peripheral blood B cells rose after LT in mice in the Iso group, but B cells were almost completely depleted by aCD20 in the blood and allograft ( Figure 7A,B).…”
Section: B Cell Depletion Attenuates Ar and Chronic Fibrosismentioning
confidence: 99%
“…For B cell depletion, 250 μg of anti-mouse CD20 antibody (clone SA271G2 Rat IgG2bκ, BioLegend, San Diego, CA) (aCD20) or isotype control rat IgG2bκ (clone RTk4530, BioLegend) (Iso) were administered intraperitoneally 2 days before and 2, 7, 14, and 21 days after LT. At this dose, SA271G2 depletes >90% of peripheral blood and secondary lymphoid organ B cells for >20 days in steady state settings, but repeat dosing is required in inflammatory contexts. 24…”
Section: Lt Procedures and Anti-cd20 Antibody Administrationmentioning
confidence: 99%
“…However, no published controlled trial exists comparing the efficacy of these approaches. Moreover, combination therapies may yield unexpected results, as suggested by Riella's work in mice showing that coadministration of IVIg with rituximab led to shortening of the half‐life of anti‐CD20 monoclonal antibody and quicker recovery of B cells . More recently, Jordan et al reported on the successful use of the IgG endopeptidase, IdES, which cleaves IgG at the Fc portion, thereby eliminating antibody‐mediated complement activation and antibody‐dependent cellular cytotoxicity.…”
Section: Treating Acute Amrmentioning
confidence: 99%
“…Using an allogeneic, syngeneic cardiac transplant model and TLR agonists, Laws et al demonstrated that inflammation mitigates B cell depletion by altering the pharmacokinetics and pharmacodynamics (PK/PD) of anti-CD20 mAb therapy leading to accelerated reconstitution of the B cell pool (23). A single dose of anti-CD20 mAb at the time of transplant fails to maintain B cell depletion.…”
Section: Introductionmentioning
confidence: 99%